No differences between Alter G-Trainer and active and passive recovery strategies on isokinetic strength, systemic oxidative stress and perceived muscle soreness after exercise-induced muscle damage - Cooke, M. B.; Nix, C. M.; Greenwood, L. D.; Greenwood, M. C. (The Journal of Strength and Conditioning Research, 2018)
The incidence of muscle injuries is prevalent in elite sport athletes and weekend warriors and strategies that safely and effectively hasten recovery are highly desirable. The purpose of this study was to examine the differences between 3 recovery methods after eliciting muscle damage in recreationally active men relative to maximal isokinetic contractions, perceived muscle soreness, and psychological mood states. Twenty-five recreationally active men (22.15 ± 3.53 years, 75.75 ± 11.91 kg, 180.52 ± 7.3 cm) were randomly matched by V[Combining Dot Above]O2 peak (53.86 ± 6.65 ml·kg-1·min-1) and assigned to one of 3 recovery methods: anti-gravity treadmill (G-Trainer) (N = 8), conventional treadmill (N = 8) or static stretching (N = 9). Recovery methods were performed 30 minutes, 24, 48, and 72 hours after a 45-minute downhill run. Following eccentrically biased running, no significant differences were noted in isokinetic knee flexion and extension peak torque, systemic markers of muscle damage, oxidative stress and lipid peroxidation such as serum creatine kinase (CK), superoxide dismutase (SOD), and malondialdehyde (MDA), respectively, and subjective ratings of perceived muscle soreness between recovery methods. The G-Trainer group did however display a higher mood state as indicated by the Profile of Mood State global scores at 24 hours postexercise when compared to the conventional treadmill recovery group (p = 0.035). The improved mood state after the use of the anti-gravity treadmill may provide clinical relevance to other populations.